The esthetics of amazing description in Quran narrative description - Mezghiche, Yamina (Journal of Human Sciences, 2021)
Description in the Quran narrative discourse is related to artistically styles based on literary image focused on the rhetoric discourse while the artistically scene move to esthestied discourse relying on the attraction of the receiver and calling for his imagination in order to receive alive scenes it has an imagination of human behavior and psychological trends as well as the dictation of conscience the essential part of these scenes is the amazing the causes surprising vacuum in one’s life experience.